Approximation of Continuous Functions by de La Vallee-Poussin Operators
For σ → ∞, we study the asymptotic behavior of upper bounds of deviations of functions blonding to the classes C_∞^Ψ and C^Ψ H_ω from the so-called Vallee Poussin operators. We find asymptotic equalities that, in some important cases, guarantee the solution of the Kolmogorov - Nikol’s’kyi problem for the Vallee Poussin operators on the classes C_∞^Ψ and C^Ψ H_ω. , number=2, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Rukasov, V. I. and Silin, E. S., year=2005, month=Feb., pages=230–238